Salmonella enterica Serovar Paratyphi C Carries an Inactive Shufflon - Tam, Connie K. P. (American Society for Microbiology, 2004)
Salmonella enterica serovar Typhi uses type IVB pili to facilitate bacterial self-association, but only when the PilV proteins (potential minor pilus proteins) are not synthesized. This pilus-mediated event may be important in typhoid fever pathogenesis. We initially show that S. enterica serovar Paratyphi C strains harbor a pil operon very similar to that of serovar Typhi. An important difference, however, is located in the shufflon which concludes the pil operon. In serovar Typhi, the Rci recombinase acts upon two 19-bp inverted repeats to invert the terminal region of the pilV gene, thereby disrupting PilV synthesis and permitting bacterial self-association. In serovar Paratyphi C, however, the shufflon is essentially inactive because each of the Rci 19-bp substrates has acquired a single base pair insertion. A PilV protein is thus synthesized whenever the pil operon is active, and bacterial self-association therefore does not occur in serovar Paratyphi C. The data thus suggest that serovar Typhi bacterial self-association using type IVB pili may be important in the pathogenesis of epidemic enteric fever.